Computational Design And Synthesis Of Potential Ns2b-Ns3 Dengue Protease Inhibitors - Salin, Nurul Hanim (2024)
DENV2, the type of dengue virus commonly found in Southeast Asia, is a major public health concern. In week 6 of 2024, Malaysia reported with 3,631 dengue cases and 10 deaths due to DENV2, marking a 68.75 % increase from the same period in 2023, as reported by the World Health Organization (WHO). Despite the high number of cases, there is currently no clinically proven drug available to inhibit the virus replication, primarily due to the limited availability of 3D crystal structures of targetable protein-protein interactions for drug activation, including the NS2B-NS3 protease from DENV2 and West Nile virus (WNV). To address this issue, docking and pharmacophore modelling have been used with the ligands from DENV2 NS2B-NS3 protease and West Nile Virus. The Systematic Literature Review (SLR) analysis identified 9 active compounds from 2 types of in vitro DENV NS2B-NS3 protease assays i.e. 21 compound classes from cell-free-based assays and 9 compound classes from cell-based assays. 2 of the 9 scaffolds' molecules were identified as the best pharmacophore model based on their high Area Under the Curve (AUC) and Enrichment Factor (EF) values, which were close to 1 and 100% respectively, and were further used as a model for pharmacophore validation.